TANGGUNG JAWAB HUKUM TERHADAP PELAKU USAHA YANG MENJUAL PARCEL PANGAN KADALUWARSA DALAM PRESPEKTIF HUKUM PERLINDUNGAN KONSUMEN - NIM. A1011211151, IDRIS (Fakultas Hukum Universitas Tanjungpura, 2025)
ABSTRACT In the current era of globalization and free trade, many products or goods are marketed to consumers, but many of these products that have expired are still sold by producers. This is certainly very detrimental to consumers because it can endanger the health and safety of consumers, besides that it is also contrary to consumer protection laws. Therefore, there needs to be an effort from the government to protect consumers through law enforcement in the field of consumer protection. Of course, this makes the author interested in raising the title of the thesis on